Development of Mass-casualty Life Support-CBRNE (MCLS-CBRNE) in Japan. Issue 5 (17th August 2016) - Anan, Hideaki; Otomo, Yasuhiro; Kondo, Hisayoshi; Homma, Masato; Koido, Yuichi; Morino, Kazuma; Oshiro, Kenichi; Harikae, Kiyokazu; Akasaka, Osamu
Abstract: This report outlines the need for the development of an advanced course in mass-casualty life support (MCLS) and introduces the course content. The current problems with education on disasters involving chemical agents, biological agents, radiation/nuclear attacks, or explosives (CBRNE) in Japan are presented. This newly developed "MCLS-CBRNE" program was created by a Ministry of Health, Labour, and Welfare (Tokyo, Japan) research group based on these circumstances. Modifications were then made after a trial course. Training opportunities for relevant organizations to learn how to act at a CBRNE disaster site currently are lacking. The developed course covers initial responses at a disaster site. This one-day training course comprises lectures, three tabletop simulations, and practical exercises in pre-decontamination triage and post-decontamination triage. With regard to field exercises conducted to date, related organizations have experienced difficulties in understanding each other and adapting their approaches. Tabletop simulations provide an opportunity for participants to learn how organizations working on-site, including fire, police, and medical personnel, act with differing goals and guiding principles. This course appears useful as a means for relevant organizations to understand the importance of developing common guidelines. The MCLS-CBRNE training is proposed to support CBRNE disaster control measures during future events. H Anan, Y Otomo, H Kondo, M Homma, Y Koido, K Morino, K Oshiro, K Harikae, O Akasaka .Development of mass-casualty life support-CBRNE (MCLS-CBRNE) in Japan .Prehosp Disaster Med .2016 ;31 (5 ):547 –550 .